1986
DOI: 10.1203/00006450-198610000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Bone Growth with Low Bone Mineral Content in Very Low Birth Weight Premature Infants

Abstract: MATERIALS AND METHODSand BW at birth. Because ofthe direct relationship between BMC and BW we speculated that the ratio of BMC to BW would be useful in identifying disorders of bone mineral metabolism in low birth weight infants (I).In the present study, we report serial measurements of BMC and BW through the first 10 wk of life in 38 VLBW premature infants. We hypothesized that during this period of active growth in weight and length, BW (a measure ofbone diameter and hence of appositional bone growth in infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 12 publications
2
27
0
3
Order By: Relevance
“…Previous longitudinal studies using single-photon absorptiometry confirmed the need for higher intakes of dietary calcium, phosphorus and vitamin D to improve bone mineralization in preterm hospitalized infants. 1,26 Although the positive effects of passive exercise on bone mineralization in preterm infants have been demonstrated, the American Academy of Pediatrics has stated that the nutritional goal for preterm infants is to provide optimal nutrition to support growth equivalent to in utero gain during the third trimester. Nutritional intervention, while promoting adequate weight gain, has variable effect on postnatal bone mineralization in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous longitudinal studies using single-photon absorptiometry confirmed the need for higher intakes of dietary calcium, phosphorus and vitamin D to improve bone mineralization in preterm hospitalized infants. 1,26 Although the positive effects of passive exercise on bone mineralization in preterm infants have been demonstrated, the American Academy of Pediatrics has stated that the nutritional goal for preterm infants is to provide optimal nutrition to support growth equivalent to in utero gain during the third trimester. Nutritional intervention, while promoting adequate weight gain, has variable effect on postnatal bone mineralization in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fracture frequency can reach 70%, especially in extreme cases involving sickly preterm infants. [1][2][3][4] The prolonged period of hospitalization of premature infants without physical stimulation may contribute to bone demineralization and can lead to changes in bone development and growth. [5][6][7][8][9] These alterations in bone development produce a reduction in both growth velocity and height, with a higher frequency of scoliosis, leg curvature and cranial deformities.…”
Section: Introductionmentioning
confidence: 99%
“…17,18,23 Infants in all three groups of this study were fed an equivalent energy and nutrient intake of fortified mother's milk at recommended levels 17 and experienced an equivalent postnatal growth rate. Earlier studies 14,15,24 reported a greater rate of postnatal weight gain in preterm VLBW infants who received daily physical activity, although energy and nutrient intakes did not diminish or differ between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The physical activity consisted of range of motion movements against passive resistance to all extremities as previously described. 17,18 The OT provided instruction and weekly review regarding the physical activity protocol and its administration to mothers of infants randomized to the MOM group. The infant's mother kept a diary to document administration of the physical activity program.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown lower bone mineral content (BMC) of the radius throughout the first 6 months of life of infants fed human milk compared with cow milk formula. 9,10 No studies have been reported on the effect of varying mineral intakes on total body bone mass accretion during the first year of life, which should be a better indicator of mineral nutriture. In addition, no studies have been designed in such a way as to determine whether early feeding during the first 6 months of life has a persistent effect on differences in bone mass accretion.…”
mentioning
confidence: 99%